Combined Increases in Mitochondrial Cooperation and Oxygen Photoreduction Compensate for Deficiency in Cyclic Electron Flow in Chlamydomonas reinhardtii . Issue 7 (2nd July 2014) - Dang, Kieu-Van; Plet, Julie; Tolleter, Dimitri; Jokel, Martina; Cuiné, Stéphan; Carrier, Patrick; Auroy, Pascaline; Richaud, Pierre; Johnson, Xenie; Alric, Jean; Allahverdiyeva, Yagut; Peltier, Gilles
Abstract : Contribution of cyclic electron flow to photosynthesis and biomass productivity is explored in a Chlamydomonas reinhardtii PGRL1-deficient mutant. Induction of different mechanisms, including cooperation between photosynthesis and mitochondrial respiration and oxygen photoreduction (direct or flavodiiron-mediated), efficiently compensates for the deficit in ATP supply under steady state, but not under transient or fluctuating conditions. Abstract: During oxygenic photosynthesis, metabolic reactions of CO2 fixation require more ATP than is supplied by the linear electron flow operating from photosystem II to photosystem I (PSI ). Different mechanisms, such as cyclic electron flow (CEF ) around PSI, have been proposed to participate in reequilibrating the ATP/NADPH balance. To determine the contribution of CEF to microalgal biomass productivity, here, we studied photosynthesis and growth performances of a knockout Chlamydomonas reinhardtii mutant ( pgrl1 ) deficient in PROTON GRADIENT REGULATION LIKE1 (PGRL1)–mediated CEF . Steady state biomass productivity of the pgrl1 mutant, measured in photobioreactors operated as turbidostats, was similar to its wild-type progenitor under a wide range of illumination and CO2 concentrations. Several changes were observed in pgrl1, including higher sensitivity of photosynthesis to mitochondrial inhibitors, increased light-dependent O2 uptake, and increased amounts of flavodiiron (FLV) proteins. We conclude that a combination of mitochondrial cooperation and oxygen photoreduction downstream of PSI (Mehler reactions) supplies extra ATP for photosynthesis in the pgrl1 mutant, resulting in normal biomass productivity under steady state conditions. The lower biomass productivity observed in the pgrl1 mutant in fluctuating light is attributed to an inability of compensation mechanisms to respond to a rapid increase in ATP demand.